Systematic review on effective psychotherapies and/or combined treatments with patients with severe and comorbidity - Scherb, Elena Diana (2024)
In the last decade, many authors have admitted that we are witnessing a change of paradigm in the way we understand evidence-based psychotherapy practice at its core. This new approach is far more idiographic, based on change processes, and a more dimensional understanding of psychopathology and human suffering. The need for changing paradigms becomes more apparent when facing patients with psychopathological symptoms that imply severity and comorbidity. The generic indication to treat these patients is combined treatment, medication, and psychotherapy. This systematic bibliographical review aims to collect scientific articles on effective psychotherapies and/or combined treatments with patients with severity and comorbidity to assess the state of the art. A secondary aim is to highlight the differences in the number of scientific publications in Latin American databases versus American and European ones. For this purpose, the author applied PRISMA declaration principles and the PICOS criterion. In the first search, the author selected 95 (N=95) articles, of which 90% of the analysis units came from databases in Europe and the United States. Then, the author conducted three other searches, which selected 53 articles (N= 53), excluding the findings of European and USA databases because they yielded results that were too extensive. Tables I, II, and III summarize the findings.